2011
DOI: 10.1155/2011/702146
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Clinical Effects of Vaccines Targeting p53‐Overexpressing Malignancies

Abstract: Approximately 50% of human malignancies carry p53 mutations, which makes it a potential antigenic target for cancer immunotherapy. Adoptive transfer with p53-specific cytotoxic T-lymphocytes (CTL) and CD4+ T-helper cells eradicates p53-overexpressing tumors in mice. Furthermore, p53 antibodies and p53-specific CTLs can be detected in cancer patients, indicating that p53 is immunogenic. Based on these results, clinical trials were initiated. In this paper, we review immunological and clinical responses observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 94 publications
(89 reference statements)
0
35
0
1
Order By: Relevance
“…There is an increasing attention to develop different strategies that can modulate p53-dependent apoptotic pathways such as inhibition of p53-MDM2 interaction using MDM2 inhibitors, restoring mutated p53 back to its wild-type form and p53 vaccines [158][159][160].…”
Section: Death Receptormentioning
confidence: 99%
“…There is an increasing attention to develop different strategies that can modulate p53-dependent apoptotic pathways such as inhibition of p53-MDM2 interaction using MDM2 inhibitors, restoring mutated p53 back to its wild-type form and p53 vaccines [158][159][160].…”
Section: Death Receptormentioning
confidence: 99%
“…In addition, numerous clinical trials have been performed using different kinds of p53 vaccines including I) short and long peptide-based vaccines, II) dendritic cellbased vaccines, and III) recombinant replication-defective adenoviral vectors with human wild-type p53 (Kuball et al, 2002;Svane et al, 2004;Vermeij et al, 2011).…”
Section: Targeting P53mentioning
confidence: 99%
“…Historically, especially within the first 20 years of p53 research, the connection of p53 with host immune response and regulation had been mostly limited to employing fragments of p53 protein as tumor-associated antigens (TAAs) for tumor vaccines [20,21,22] because many forms of p53 mutation stabilize the p53 protein, resulting in elevated p53 level in tumors [1,3,23,24]. Recently, our studies and those of others have shown that p53 inactivation/dysfunction alters the immune landscape of the tumor microenvironment (TME) towards pro-tumor inflammation [25,26,27,28], whereas p53 reactivation or restoration changes the milieu of TME to promote antitumor immunity [29,30,31].…”
Section: Introductionmentioning
confidence: 99%